Effects of an intervention in eating habits and physical activity in Japanese-Brazilian women with a high prevalence of metabolic syndrome in Bauru, São Paulo State, Brazil Efeitos da intervenção em hábitos alimentares e atividade física de mulheres nipo-brasileiras com elevada prevalência de síndrome metabólica, residentes em Bauru, São Paulo, Brasil - Sandra Roberta G. Ferreira; Suely G. A. Gimeno; Amélia T. Hirai; Helena Harima; Luiza Matsumura; Bianca de Almeida Pittito (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
We evaluated the impact of a lifestyle intervention on the cardiometabolic risk profile of women participating in the Study on Diabetes and Associated Diseases in the Japanese-Brazilian Population in Bauru. This was a non-controlled experimental study including clinical and laboratory values at baseline and after a 1-year intervention period. 401 Japanese-Brazilian women were examined (age 60.8±11.7 years), and 365 classified for metabolic syndrome (prevalence = 50.6%). Subjects with metabolic syndrome were older than those without (63.0±10.0 vs. 56.7±11.6 years, p < 0.01). After intervention, improvements in variables were found, except for C-reactive protein. Body mass index and waist circumference decreased, but adiposity reduction was more pronounced in the abdominal region (87.0±9.7 to 84.5±11.2cm, p < 0.001). Intervention-induced differences in total cholesterol, LDL, and post-challenge glucose were significant; women who lost more than 5% body weight showed a better profile than those who did not. The lifestyle intervention in Japanese-Brazilian women at high cardiometabolic risk improved anthropometric and laboratory parameters, but it is not known whether such benefits will persist and result in long-term reduction in cardiovascular events. Avaliou-se o impacto de intervenção no estilo de vida no perfil de risco cardiometabólico de mulheres participantes do Estudo de Diabetes e Doenças Associadas na População Nipo-Brasileira de Bauru. O delineamento foi experimental não-controlado, incluindo avaliação clínico-laboratorial basal e um ano após a intervenção. Examinaram-se 401 nipo-brasileiras (60,8 ± 11,7 anos) sendo 365 classificáveis quanto à presença de síndrome metabólica, estimada em 50,6%. Portadoras de síndrome metabólica eram mais velhas que aquelas sem a síndrome (63,0 ± 10,0 vs. 56,7 ± 11,6 anos; p < 0,01). A intervenção associou-se à melhora nas variáveis avaliadas exceto na proteína C reativa. O índice de massa corporal e a cintura caíram, sendo a redução da adiposidade mais marcante na região abdominal (87,0 ± 9,7 para 84,5 ± 11,2cm; p < 0,001). As diferenças induzidas pela intervenção nos níveis de colesterol total, LDL e glicose pós-sobrecarga foram significantes; mulheres que reduziram > 5% do peso apresentaram melhor perfil que as que mantiveram ou ganharam. Programa de intervenção no estilo de vida em nipo-brasileiras de alto risco cardiometabólico, melhorou o perfil antropométrico e bioquímico, porém, se desconhece se serão duradouros, reduzindo eventos cardiovasculares em longo prazo.